Tourist Perception and Satisfaction on Food and Environment in Nusa Dua Tourism Area - Dewa Made Suria Antara; Ni Nyoman Triyuni; Ni Gst Nym Suci Murni (Soshum: Jurnal Sosial dan Humaniora, 2018)
The tourism industry is strongly influenced by the perception and satisfaction of tourists towards a destination. Perception is considered in conjunction with dynamic tourist expectations and perceptions. They are changing, so it is important to measure the tourist perception routinely. Perception is used as a base by travellers for assessing the quality of services rendered to them. This study aims at assessing the perception of tourists to some of the attributes of the Nusa Dua Tourism area and measuring tourist satisfaction against some of these attributes. The attributes to be measured are: environment and food. This research is a quantitative research. It employs questionnaires to collect data. Data were collected from 280 respondents who were selected through random sampling. The descriptive statistics (frequency, percentage, and average) and Importance-Performance Analysis (IPA) are employed to determine the perception and satisfaction of tourists towards the attributes of environmental and food at the Nusa Dua Tourism area. The result showed that Nusa Dua area management had provided excellent service to the two attributes and had considered them as important components in delivering satisfaction with their visit in Nusa Dua tourism area. The findings, from a marketing perspective is as a basis for the management of the Nusa Dua Tourism area in making policies for the improvement of the region, especially in meeting the tourists’ perception and satisfaction.